The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1542/peds.108.4.965
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Islamic Biomedical Ethics: A Primer for the Pediatrician

Abstract: The United States is becoming increasingly pluralistic. Pediatricians must become familiar with the factors that affect the emotional, physical, and spiritual health of their patients that are outside the kin of the traditionally dominant value system. Although many articles have addressed the cultural and ethnic factors, very few have considered the impact of religion. Islam, as the largest and fastest-growing religion in the world, has adherent throughout the world, including the United States, with 50% of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 15 publications
0
51
1
Order By: Relevance
“…Like Christianity and Judaism, Islam acknowledges that the death is the inevitable phase of life of human beings. Medical management should not be given if it prolongs the final stage of a terminal illness as opposed to treating a superimposed, life-threatening condition 9 . However, Islam believes that all healing comes from God, so Man has an obligation to search medical care and right to receive appropriate medical treatment 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Like Christianity and Judaism, Islam acknowledges that the death is the inevitable phase of life of human beings. Medical management should not be given if it prolongs the final stage of a terminal illness as opposed to treating a superimposed, life-threatening condition 9 . However, Islam believes that all healing comes from God, so Man has an obligation to search medical care and right to receive appropriate medical treatment 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study the results revealed that, the most common reasons against continuation of practice were; no religious support, painful and unhealthy procedure, unnecessary for girl, bad social habit and health consequences related to it, in agreement with other studies (8,9,23,35) . FGM is performed for reasons that include; sexual (to control or reduce female sexuality), sociological (as an initiation for girls into womanhood, social integration and the maintenance of social cohesion), hygiene and aesthetic reasons (due to a belief that the female genitalia are dirty and unsightly), health (in the belief that it enhances fertility and child survival) and for religious reasons-due to the mistaken belief that it is a religious requirement (33) . The girls in the current study were asked for reasons support the practice of FGM and they answered that circumcision is an important religious requirement, cultural and social traditional, restraining sexual desire, cleanliness for girls, chastity and evidence of feminist, in agreement with other studies (8,9,20) .…”
Section: Prevalence Of Female Genital Mutilation Among School Girls Imentioning
confidence: 99%
“…Thus, e.g., Kamyar M. Hedayat and Roya Pirzadeh, both pediatricians, counsel from a Shi'a Islamic perspective that, "When there are 2 equivalent treatments, and an intellectually mature teenager chooses one and his father chooses the other one and they cannot be reconciled, the physician may respect the decision of his patieht (Ayatollahs Sistani and N. Makarem-Shirazi, personal communication, June 1999)." 39 Whether such a view applies in the Sunni Islamic setting of contemporary Bangladesh would require further evaluation in relation to the dominant Hanafi and Salafi perspectives now influencing jurisprudential decision among religious authorities.…”
Section: The Islamic Ethical Viewmentioning
confidence: 99%
“…and alleviation of symptoms (physical therapy with range-of-motion and progressive resistive exercise; medication (corticosteroids in Bangladesh are available at a cost of BDT250 per 100 20 mg. tablets, equivalent to US$3.11 cost), 9 with special education service for developmental disability. These services are of such cost that Mr. Hossain cannot afford either the assistive devices or the medication for the three individuals, not to mention the problem of managing their care at home without others within the family to assist with regularity.…”
Section: Introductionmentioning
confidence: 99%